2004
DOI: 10.1002/cncr.20080
|View full text |Cite
|
Sign up to set email alerts
|

Survival among women with borderline ovarian tumors and ovarian carcinoma

Abstract: BACKGROUND. Serous and mucinous ovarian tumors of low malignant potential (LMP-S and LMP-M, respectively) are noninvasive tumors that portend excellent survival when confined to the ovary. Comparison of the survival for women with LMP tumors staged as distant with women who have carcinoma may have important implications for diagnostic terminology and clinical management. METHODS. The authors compared relative survival rates among patients diagnosed with ovarian tumors during the period 1988-1999 (with follow-u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

6
100
0
14

Year Published

2005
2005
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 165 publications
(120 citation statements)
references
References 40 publications
6
100
0
14
Order By: Relevance
“…A more recent study by Trimble et al (2002) found FIGO stage to be associated with survival in 2818 women with borderline ovarian tumours. Similarly, Sherman et al (2004) reported reduced 10 year survival in distant stage vs localised disease in a group of approximately 4500 borderline ovarian cancer patients. To date, there have been few comprehensive analyses of molecular determinants of prognosis.…”
Section: Discussionmentioning
confidence: 90%
“…A more recent study by Trimble et al (2002) found FIGO stage to be associated with survival in 2818 women with borderline ovarian tumours. Similarly, Sherman et al (2004) reported reduced 10 year survival in distant stage vs localised disease in a group of approximately 4500 borderline ovarian cancer patients. To date, there have been few comprehensive analyses of molecular determinants of prognosis.…”
Section: Discussionmentioning
confidence: 90%
“…It has been shown that the 5-year survival rate was 95 -97% for stage I and 65 -87% for stages II and III (Trope et al, 2000;Trimble et al, 2002;Sherman et al, 2004) suggesting that the prognosis for borderline ovarian tumours depends on extraovarian extension of the tumour. In addition, prognostic factors included clinical stage, histopathological subtype, and residual tumour, but the surgical method was not regarded as a prognostic factor (Trope et al, 2000;Gilks, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Although less common, advanced MOC is associated with a very poor survival that surpasses the poor prognosis for women with advanced stage serous ovarian cancer (Sherman et al, 2004). Accumulating pathological and epidemiological evidence supports a progression model of MOC, from benign cysts to borderline tumours to invasive adenocarcinoma (Feeley and Wells, 2001;Shih and Kurman, 2004).…”
mentioning
confidence: 98%
“…The majority of mucinous ovarian cancers (MOC) are diagnosed at an early stage, either as borderline (atypical proliferative) tumours or low-grade carcinomas, and have an excellent prognosis (Sherman et al, 2004). Although less common, advanced MOC is associated with a very poor survival that surpasses the poor prognosis for women with advanced stage serous ovarian cancer (Sherman et al, 2004).…”
mentioning
confidence: 99%